2004
DOI: 10.1007/s00122-004-1725-6
|View full text |Cite
|
Sign up to set email alerts
|

Reduced metaphase I associations between the short arms of homoeologous chromosomes in a Hordeum vulgare L. � H. bulbosum L. diploid hybrid influences the frequency of recombinant progeny

Abstract: Hordeum vulgare (cultivated barley) x H. bulbosum (bulbous barley grass) hybrids have been used to obtain disease-resistant recombinant lines (RLs). The RLs contain chromatin transferred from the wild species mostly onto the long arms of recipient barley chromosomes. To determine whether differences in meiotic metaphase I (MI) associations between the long and short arms of homologous chromosomes can account for the preponderance of introgressions on the long arms, we carried out fluorescent in situ hybridisat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
11

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 31 publications
0
8
1
11
Order By: Relevance
“…This observation agrees with the work of Pickering et al [2006a] who investigated the chromosome pairing frequency of 2 diploid Hv × Hb hybrids. In contrast to our results regarding the frequency of Hv -Hb pairing of long and short arms of particular chromosomes, Pickering et al [2004] observed differences only in short-arm pairing. Frequencies of long-arm pairing were similar for Hv chromosomes 1H, 2H, 4H, 5H, and 6H.…”
Section: Homoeologous Pairing In Hybrids and Recombinants In Offspringcontrasting
confidence: 56%
See 2 more Smart Citations
“…This observation agrees with the work of Pickering et al [2006a] who investigated the chromosome pairing frequency of 2 diploid Hv × Hb hybrids. In contrast to our results regarding the frequency of Hv -Hb pairing of long and short arms of particular chromosomes, Pickering et al [2004] observed differences only in short-arm pairing. Frequencies of long-arm pairing were similar for Hv chromosomes 1H, 2H, 4H, 5H, and 6H.…”
Section: Homoeologous Pairing In Hybrids and Recombinants In Offspringcontrasting
confidence: 56%
“…Fig. 1e, f) as reported by Pickering et al [2004]. The chromosome 1Hv was identified by weak proximal FISH signals on the short arm (online suppl.…”
Section: Identification Of Chromosomes By Fish Using 5smentioning
confidence: 67%
See 1 more Smart Citation
“…FISH with selected probes has also allowed identification of allosyndetic MI pairing for specific chromosomes (Pickering et al, 2004). This is highlighted by the study of Cuadrado et al (1997) who individually recognized the whole chromosome complement of wheat !…”
Section: Potential Of Crop-to-wild Genetic Transfermentioning
confidence: 97%
“…The whole chromosome complement of some crop species can be individualized by sequential FISH using appropriate sets of selected repeated DNA probes (Cuadrado et al, 1997;Irigoyen et al, 2002). However, only a few chromosomes are marked in most instances (e.g., Pickering et al, 2004). Combination of repeated and genomic probes has been demonstrated to be a great improvement in identification of particular chromosomes and chromosomal segments in multigenomic materials (Dong et al, 2001;Maluszynska and Hasterok, 2005;Cifuentes et al, 2006;Herrera et al, 2007) ( Figs.…”
Section: Cytomolecular Methodsmentioning
confidence: 99%